Comparison of learning style for engineering and non-engineering students - Mohaffyza, Mimi; Md Yunos, Jailani; Yee, Mei Heong; Junita, Junita; Rizal, Fahmi; Ibrahim, Badaruddin (2021)
Educators Ishould Ibe Iconsidered Ithe Ilearning Istyle Iof Istudents Iso Ithat Ithe Ibest Ipractice Iapproach Ican Ibe Iapplied Iin Ilearning Iactivities. IAs Istudents Iunderstand Itheir Ilearning Istyle, Ithey Iwill Ibe Iable Ito Iintegrate Iit Iinto Itheir Ilearning Iprocess. IKolb ILearning IStyle Iwas Ithe Ilearning Istyle Ithat Iwas Iwidely Iused Ibased Ion Ithe Itheory Iof Ilearning Iexperiences. ITherefore, Ithis Istudy Iaimed Ito Idescribe Iengineering Iand Inon-engineering Istudents’ Ilearning Istyle. IThe Isurvey Iresearch Idesign Iwith Ia Iquantitative Iapproach Iwas Iapplied Iin Ithis Istudy. IA Itotal Iof I300 Irespondents Iwere Iselected Irandomly Ifrom Iall Ifaculties Iin IUniversiti ITun IHussein IOnn IMalaysia. IThe Isurvey Iquestionnaire Iconsisted Iof Itwo Imain Isections Irepresenting ILearning IGoals, ILearning IStyle, Iand ILearning IActivities. IThe Iresult Iexplains Ithat Iboth Iengineering Iand Inon-engineering Istudents Iare Imore Idominant Ito Iadopt Ithe IAccommodator Ilearning Istyle, followed Iby Ithe IConverger Ilearning Istyle, and Ithen IAssimilator Ilearning Istyle and IDiverger Ilearning Istyle. I IIt Iis Iconcluded Ithat Ithe Iengineering Iand Inon-engineering Istudents Iare Imore Iincline Ito Ibe Ia Ikinesthetic Ilearner. IThese Ilearning Ipreferences Iand Ilearning Istyles Iwill Icontribute Ito Itheir Iengagement Iin Ithe Iconcept Iof Ilearning and for educators to plan teaching strategies.